Environmental disclosure quality: Evaluating the effectiveness of the second edition of the sustainability reporting guide - Al-Rowaidi, Magdi Abdoh Sagheer (2021)
In late 2018, Bursa Malaysia, a self-regulatory body that governs Malaysian public listed companies, issued the second edition of the Sustainability Reporting Guide (SRG-2) to improve the quality of sustainability disclosure. This study took the initiative and empirically evaluated the effectiveness of the SRG-2 to improve the environmental disclosure quality (EDQ). Therefore, this study compared the EDQ before and after the issuance of SRG-2 to determine the effectiveness of this new guide. Content analysis was utilized to extract the environmental data from 43 plantation companies. The EDQ was measured using an adopted disclosure index and a scoring system to transmit the environmental information to measurable data. For maintaining strong robustness, this study uses two methods of assessing the significance: parametric (paired sample t-test) and non-parametric (Wilcoxon-signed rank test). Overall, this study is in the same boat as prior studies when the findings revealed that the EDQ is still low compared to the overall potential score. However, the results indicated a statistically significant increase in EDQ in 2019 compared to its equivalent in 2017. Therefore, it can be confirmed that SRG-2 is effective and contributed to improving EDQ. Furthermore, the results provide some supports for both legitimacy and stakeholder theories.